Realizability of some Böröczky arrangements over the rational numbers - Janasz, Marek; Lampa-Baczynska, Magdalena; Wójcik, Daniel (Analitic and Algebraic Geometry 4, 2022)
In this paper, we study the parameter spaces for Böröczky arrangements Bn of n lines, where n < 12. We prove that up to n = 12, there exist only one arrangement nonrealizable over the rational numbers, that is B11.